Characteristics of direct shear test for plain concrete joint with rubber cushion - Zhang Zhenyu; Li Haojie; Jia Changheng; Feng Jili (矿业科学学报, 2018)
The contact friction between the segments and the joints of shield segments plays a crucial role in the stability of the shield segment.In order to analyze the contact friction among tunnel segments,direct shear tests were carried out on concrete specimens with rubber.The experimental results show that the response of shear stress with respect to shear displacement for specimens only contact with concrete can be regarded as elastic phase,elastoplastic hardening phase,and the interface is still in perfect plastic state after the shear stress reaches the peak.When the specimen is affixed with rubber cushion,the rubber has a cushion effect on the concretes and can release the shear stress at the interface accompanied by significant strain softening.When axial pressures are in the range of 1.5-13 MPa,the ratio of residual strength with respect to shear stress strength is about 55%-65%.When axial pressures are 17 MPa and 21 MPa,the ratio of residual strength with respect to shear stress strength are about 70% and 80%,respectively.Archard nonlinear friction power law is used to describe the behavior of peak shear stress and axial stress at the interface.The experimental results show that the relationship between shear stress and shear displacement for different interfaces,which can be used to study contact friction of similar contact surfaces.